Common practices of Speech and language pathologists about partner oriented training to treat aphasia - Fazaila Ehsaan; Mumtaz, Nazia (Journal of the Pakistan Medical Association, 2024)
Objective: To find the common practices among speech language pathologists regarding partner-oriented training for aphasic patients. Method: The exploratory, qualitative study was conducted at Riphah International University, Lahore, Pakistan, from March 1 to May 31, 2021, and comprised speech language pathologists working with aphasiac patients for at least 5 years in Lahore, Karachi and Islamabad. Data was collected using a structured interview guide that were conducted online. The recorded interviews were transcribed, and the data was subjected to thematic analysis. Result: Of the 10 subjects, 6(60%) were females and 4(40%) were males. Overall, 6(60%) subjects had professional experience of >10 years. Thematic analysis showed that most of the speech language pathologists used traditional approaches for aphasia treatment, and counselling of patient’s caregiver was done. However, there was no formal tool in Urdu language to provide basic communication strategies for the patient’s caregivers or their communication partners. The participants recommended efforts to develop such a tool. Conclusion: There was found a dire need of communication partner training (CPT) programme for aphasia patients and their significant others with appropriate linguistic and cultural norms to facilitate them with the aim of improving their quality of life. Key Words: Aphasia, Quality of life, Speech therapies, Acquired communication disorder, Partner communication.